2024
DOI: 10.5477/cis/reis.172.101
|View full text |Cite
|
Sign up to set email alerts
|

Presión y fraude fiscales, predisposición a pagar impuestos y satisfacción personal en España

Abstract: El principal objetivo de este trabajo es analizar el beneficio percibido por el pago de impuestos en España y la satisfacción personal, en función de la predisposición a pagar impuestos, de la presión y fraude fiscales percibidos. Se propone un modelo de ecuaciones estructurales y se utilizan datos de la encuesta sobre opinión pública y política fiscal del Centro de Investigaciones Sociológicas (CIS). Los resultados confirman que la satisfacción personal está relacionada con el beneficio percibido por el pago … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…But these public services, as argued by Grönroos (1984), must be functional and of high quality. Novo et al. (2020) found that a good opinion of social services in Spain positively influences both the payment of taxes and the good opinion of the use of these assets obtained.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 97%
See 4 more Smart Citations
“…But these public services, as argued by Grönroos (1984), must be functional and of high quality. Novo et al. (2020) found that a good opinion of social services in Spain positively influences both the payment of taxes and the good opinion of the use of these assets obtained.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 97%
“…These fundamental needs for society are access to education, health, housing and security, among others (Vargas, 2020), considered by many citizens to be part of the welfare state that should be provided by public administrations (Calero, 2021). The perceived benefit of social services paid for by taxes has a positive influence on personal satisfaction (Novo et al. , 2020).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations